Penyuluhan Metode Pembayaran QRIS/Scan QR Code pada Pelaku UMKM di Desa Banjarwati Kec. Paciran - Tito Nur Mustika; Setyowati, Suci Yongki; Ismiasih, Novi (Opportunity Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
Cash payments using currency, especially banknote, are often used in buying and selling transactions. Sometimes paying for banknote makes the seller confused about finding change, if the nominal value of the banknote is too large compared to the price of the item. Business actors must also increase their vigilance against the rise of counterfeit banknote. With the QRIS (Quick Response Code Indonesian Standard) payment method, it is hoped that business actors will not have to be confused about looking for change or worry about counterfeit money being widely circulated. There are many benefits of QRIS, such as increasing sales, practical, efficient, safe in transactions, increasing business popularity. Therefore, the service team provides outreach to business actors. The counseling aims to introduce and explain the importance of having QRIS. The team used communicative and interview methods. Business people are very enthusiastic about having QRIS after the team gave a presentation about the QRIS payment method.